Effect of Path Loss Propagation Model on the Position Estimation Accuracy of a 3-Dimensional Minimum Configuration Multilateration System - Shehu Yaro, Abdulmalik; Zuri Sha'ameri, Ahmad (International Journal of Integrated Engineering, 2018)
The 3-Dimensional (3-D) position estimation (PE) accuracy of a multilateration (MLAT) system depends on several factors one of which is the accuracy at which the time difference of arrival (TDOA) measurements are obtained. In this paper, signal attenuation is considered the major contributor to the TDOA estimation error and the effect of the signal attenuation based on path loss propagation model on the PE accuracy of the MLAT system is determined. The two path loss propagation models are considered namely: Okumura-Hata and the free space path loss (FSPL) model. The transmitter and receiver parameters used for the analysis are based on actual system used in the civil aviation. Monte Carlo simulation result based on square ground receiving station (GRS) configuration and at selected aircraft positions shows that the MLAT system with the Okumura-Hata model has the highest PE error. The horizontal coordinate and altitude error obtained with the Okumura-Hata are 2.5 km and 0.6 km respectively higher than that obtained with the FSPL model